Conceptual and preliminary design methods for use on conventional and blended wing body airliners - Smith, Howard; Fielding, John (Cranfield University, 2019)
Transcript of John Fielding and Howard Smith's 1999 lecture to Court, Cranfield University.
Keywords: aircraft conceptual design'; 'aircraft preliminary design'; 'conventional airliners'; 'blended wing body airliners'; 'BWB'; 'Aerospace Structures'; 'Aerospace Engineering'